Exradin W1 plastic scintillation detector for in vivo skin dosimetry in passive scattering proton therapy. (March 2018) - Alsanea, Fahed; Wootton, Landon; Sahoo, Narayan; Kudchadker, Rajat; Mahmood, Usama; Beddar, Sam
Highlights: In vivo skin dosimetry method for proton therapy. Used the commercially available Exradin W1 plastic scintillation detector. In vivo measurements were compared to in-phantom ion chamber measurements. Method did not alter patient treatment plans and treatment workflow. Abstract: In vivo skin dosimetry is desirable in passive scattering proton therapy because of the possibility of high entrance dose with a small number of fields. However, suitable detectors are needed to determine skin dose in proton therapy. Plastic scintillation detectors (PSDs) are particularly well suited for applications in proton therapy because of their water equivalence, small size, and ease of use. We investigated the utility of the Exradin W1, a commercially available PSD, for in vivo skin dosimetry during passive scattering proton therapy. We evaluated the accuracy of the Exradin W1 in six patients undergoing proton therapy for prostate cancer, as part of an Institutional Review Board-approved protocol. Over 22 weeks, we compared in vivo PSD measurements with in-phantom ionization chamber measurements and doses from the treatment planning system, resulting in 96 in vivo measurements. Temperature and ionization quenching correction factors were applied on the basis of the dose response of the PSD in a phantom. The calibrated PSD exhibited an average 7.8% under-response (±1% standard deviation) owing to ionization quenching. We observed 4% under-response at 37 °C relative to the calibration-temperature response. After temperature and quenching corrections were applied, the overall PSD dose response was within ±1% of the expected dose for all patients. The dose differences between the PSD and ionization chamber measurements for all treatment fields were within ±2% (standard deviation 0.67%). The PSD was highly accurate for in vivo skin dosimetry in passively scattered proton beams and could be useful in verifying proton therapy delivery.